Kasibu, Nueva Vizcaya’s readiness for homestay expansion towards ASEAN homestay standards - Roy O. Allawas; Joan Nebrida; Xyra Mae B. Corpuz; Daisyrel Joy D. Palayao; Shenalyn A. Pugong; Princess Meliza Junette O. Way-as (Journal of Rural Tourism, 2026)
Purpose – This study aims to examine the level of readiness of Kasibu for homestay expansion based on the ASEAN Homestay Standards, with a focus on host capabilities, accommodation quality, management practices, sustainability initiatives, and operational dimensions, as well as to analyse the relationship between readiness and perceived development challenges. Design/Methodology/Approach – A quantitative descriptive–correlational design was employed. Data were collected from 68 respondents, including local residents from Binogawan and Capisaan and municipal tourism staff, using a structured survey instrument based on ASEAN Homestay Standards. The instrument demonstrated high reliability (Cronbach’s alpha = 0.93). Descriptive statistics (mean and standard deviation) and Pearson’s product–moment correlation were used to analyse readiness levels and their relationship with perceived challenges.Findings – The results indicate moderate to high readiness for homestay development, particularly in host capabilities and location sustainability, while lower readiness is observed in sustainability initiatives and marketing. Perceived challenges are high across environmental, economic, and socio-cultural dimensions. A significant positive relationship between readiness and perceived challenges suggests that greater awareness of challenges corresponds with more cautious readiness among stakeholders.Originality/Value – This study provides empirical insights into community readiness and sustainability challenges in a rural Philippine context. It offers practical implications for policymakers and local stakeholders to enhance capacity-building, environmental management, marketing strategies, and institutional support to align with ASEAN Homestay Standards and ensure sustainable homestay development.